2020
DOI: 10.4236/ojn.2020.109060
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Coronavirus on Staff Nurses’ Feeling While Giving Direct Care to COVID-19 Patients in Various COVID Facilities

Abstract: Background: Nurses are very important frontline health care professionals as they spend more time with patients than other professionals. This is even more so at this critical time of the COVID-19 pandemic. The nursing profession is facing great challenges in coping with the pandemic as they are more vulnerable to exposure and infection with the disease. Kuwait is not spared from the global pandemic which has put the health sector under immense pressure. Because COVID-19 is highly transmissible and deadly, it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Similarly, studies in the literature states that there is a relation between the fear level of COVID-19 of the civil population and their age; that older adult population has higher fear than youngers. 52 , 53 , 54 In their cross-sectional and descriptive study, Taghaddom et al 55 from Kuwait investigated the impact of the pandemic on nurses working in COVID-19 units and reported that although nurses’ psychological responses were better with their age and duration of nursing experiences, some of them were crying at work and experiencing fear. According to the results, it is understandable that older nurses are more fearful when caring for COVID-19 patients, given that COVID-19 infection mortality rises with patient age.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, studies in the literature states that there is a relation between the fear level of COVID-19 of the civil population and their age; that older adult population has higher fear than youngers. 52 , 53 , 54 In their cross-sectional and descriptive study, Taghaddom et al 55 from Kuwait investigated the impact of the pandemic on nurses working in COVID-19 units and reported that although nurses’ psychological responses were better with their age and duration of nursing experiences, some of them were crying at work and experiencing fear. According to the results, it is understandable that older nurses are more fearful when caring for COVID-19 patients, given that COVID-19 infection mortality rises with patient age.…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that prolonged working hours has a negative correlation to emotional (r-0.165), behavioural (r-0.177), and physical (r-0.155) dimension of the nurses at 0.01 level using Spearman's correlation. Yet, one more previous study demonstrated that mean depression, anxiety, and stress scale score was 33.4 (Taghaddom et al, 2020). The mean post-traumatic stress disorder scale was 29.3.…”
Section: Discussionmentioning
confidence: 94%